Assembly of a Complex Branched Oligosaccharide by Combining Fluorous‐Supported Synthesis and Stereoselective Glycosylations using Anomeric Sulfonium Ions. Issue 37 (6th August 2015) - Huang, Wei; Gao, Qi; Boons, Geert‐Jan
Abstract There is an urgent need to develop reliable strategies for the rapid assembly of complex oligosaccharides. This paper presents a set of strategically selected orthogonal protecting groups, glycosyl donors modified by a (S)‐phenylthiomethylbenzyl ether at C‐2, and a glycosyl acceptor containing a fluorous tag, which makes it possible to rapidly prepare complex branched oligosaccharides of biological importance. The C‐2 auxiliary controlled the 1, 2‐cis anomeric selectivity of the various galactosylations. The orthogonal protecting groups, 2‐naphthylmethyl ether (Nap) and levulinic ester (Lev), made it possible to generate glycosyl acceptors and allowed the installation of a crowded branching point. After the glycosylations, the chiral auxiliary could be removed using acidic conditions, which was compatible with the presence of the orthogonal protecting groups Lev and Nap, thereby allowing the efficient installation of 1, 2‐linked glycosides. The light fluorous tag made it possible to purify the compounds by a simple filtration method using silica gel modified by fluorocarbons. The set of building blocks was successfully employed for the preparation of the carbohydrate moiety of the GPI anchor of Trypanosoma brucei, which is a parasite that causes sleeping sickness in humans and similar diseases in domestic animals.